Time-related underemployment in Turkish labor market - ERİŞ DERELİ, BİLGE (IJOPEC Publication, 2021)
Underemployment has been an important labor market indicator as well as employment rate, unemployment rate and labor force participation rate over the last decades. This study uses the Household Labor Force Surveys between 2009 and 2020 to analyze the evolution and determinants of underemployment in Turkish Labor Market. TURKSTAT’s time-related underemployment definition is used to define underemployment. Time-related underemployment involve people employed in the reference week, who actually worked less than 40 hours and are willing to work extra hours and are available to do so. Heckman’s two-stage estimation methodology is adopted to examine the impact of individual, firm and occupational characteristics on underemployment. Statistics indicate that underemployment rate jumped to 4% in 2020. Moreover, being a female, acquiring higher education level, being married, working in bigger firms, working in firms operating in the public sector are the factors that decrease the likelihood of being underemployed. The relationship between underemployment and age displays an inverted U-shape. There is a positive association between working in a permanent job relative to a temporary job and the likelihood of being underemployed.
Keywords: Underemployment; Heckman selection; Turkish Household Labor Force Surveys